Изменение изотопного состава солей лития и магния в процессе зонной перекристаллизации - Егоров Н. Б. Николай Борисович; Акимов Д. В. Дмитрий Васильевич; Жерин И. И. Иван Игнатьевич; Обмуч К. В. Кирилл Васильевич; Усов В. Ф. Владимир Фёдорович (2015, 2015)
Заглавие с экрана